PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN DAN VOLUME PERDAGANGAN (Studi Pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2017-2020) - Larangga Wildan Tanzul Fikri; Junaidi Junaidi; Hariri Hariri (e_Jurnal Ilmiah Riset Akuntansi, 2022)
The purpose of this study was to determine the effect of Corporate Social Responsibility on company value and the trading volume. The population in this study were all manufacture company food and drink sub sector that listed on IDX for the period 2017 until 2020. The sample used was 13 company samples that met the criteria for the research subject in 2021. The analytical method used was simple linear regression, normality test, descriptive statistical analysis, and hypothesis testing. The results of the study indicate that Corporate Social Responsibility affect company value and the trading volume.Keywords: Corporate Social Responsibility, Company Value, and Trading Volume